2017
DOI: 10.1002/joc.5283
|View full text |Cite
|
Sign up to set email alerts
|

Does applying quantile mapping to subsamples improve the bias correction of daily precipitation?

Abstract: Quantile mapping (QM) is routinely applied in many climate change impact studies for the bias correction (BC) of daily precipitation data. It corrects the complete distribution, but does not correct for errors in the annual cycle. Therefore, QM is often applied separately to temporal subsamples of the data (e.g. each calendar month), which reduces the calibration sample size. The question arises whether this sample size reduction negates the benefit from applying QM to temporal subsamples. We applied four QM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…However, there are particular PP and WG methods with a similar performance. In this work we found that, in agreement with previous studies (Reiter, Gutjahr, Schefczyk, Heinemann, & Casper, ), introducing a seasonal component (e.g., training the methods separately each calendar season, month or moving window) improves the results. However, we found that all implementations (even a daily moving window) resulted in a relevant performance improvement, differently to Reiter et al (), where seasons were recommended for calibration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are particular PP and WG methods with a similar performance. In this work we found that, in agreement with previous studies (Reiter, Gutjahr, Schefczyk, Heinemann, & Casper, ), introducing a seasonal component (e.g., training the methods separately each calendar season, month or moving window) improves the results. However, we found that all implementations (even a daily moving window) resulted in a relevant performance improvement, differently to Reiter et al (), where seasons were recommended for calibration.…”
Section: Discussionmentioning
confidence: 99%
“…In this work we found that, in agreement with previous studies (Reiter, Gutjahr, Schefczyk, Heinemann, & Casper, ), introducing a seasonal component (e.g., training the methods separately each calendar season, month or moving window) improves the results. However, we found that all implementations (even a daily moving window) resulted in a relevant performance improvement, differently to Reiter et al (), where seasons were recommended for calibration. The deterministic or stochastic nature of the method was the most relevant factor (together with seasonal training) for explaining the variability of results for biases in the standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…A MAE value close to 0 indicates an unbiased prediction. Both the root mean square error (RMSE) and the mean absolute error (MAE) have extensively been employed in climate change and hydrological model evaluation studies [2,6,29,[98][99][100][101][102].…”
Section: Bias Correction Implementation and Performance Assessmentmentioning
confidence: 99%
“…(), among others. One of the most popular BC methods is quantile mapping (QM) (Gudmundsson et al ., ; Cannon et al ., ; Miao et al ., ; Reiter et al ., ). QM adjusts the cumulative distribution function (CDF) of the RCMs simulations to the CDF of the observations.…”
Section: Introductionmentioning
confidence: 97%